Prevalence and risk factors of poor subjective sleep quality in elite judo athletes - Monma, T.; Matsui, T.; Inoue, K.; Masuchi, K.; Okada, T.; Tamura, M.; Ishii, T.; Satoh, M.; Tokuyama, K.; Takeda, F. (Sleep and Biological Rhythms, 2023)
This study aimed to determine the prevalence and risk factors of poor subjective sleep quality in elite judo athletes. A subjective cross-sectional questionnaire survey was conducted with 106 elite judo athletes who participated in the training camp of the Japanese national team. Eighty-six respondents (men: 52.3%; average age: 22.9 ± 3.1 years) with complete responses were included in the analysis (valid response rate: 81.1%). Subjective sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI). The prevalence of poor sleep quality (PSQI score = 5.5), the mean PSQI score, and subscale scores were investigated. Relationships between poor sleep quality and attributes, lifestyle habits, competition-based activities, and psychological distress were explored using Fisher`s exact tests and multivariate logistic regression analysis. Thirty-five respondents (40.7%) reported poor sleep quality. The percentage and subscale scores of the respondents for sleep latency, sleep duration, and daytime dysfunction were higher than those of the population of Japanese national-level athletes. The mean PSQI score of the respondents was similar to that of some elite athlete populations but higher than those of others. Multivariate logistic regression analysis revealed that psychological distress was associated with poor sleep quality. In conclusion, the prevalence of poor subjective sleep quality in elite judo athletes was suggested to be similar or higher among elite athlete population. Sleep latency, sleep duration, and daytime dysfunction status were worse in elite judo athletes than in Japanese national-level athletes. Psychological distress was a risk factor for poor subjective sleep quality in elite judo athletes.